Impact of Treatment Regimens on Antibody Response to the SARS-CoV-2 Coronavirus - Shang, Yufeng; Liu, Tao; Li, Jingfeng; Kaweme, Natasha Mupeta; Wang, Xinghuan; Zhou, Fuling (Frontiers in Immunology, 2021)
The coronavirus disease 2019 (COVID-19) is widely spread and remains a global pandemic. Limited evidence on the systematic evaluation of the impact of treatment regimens on antibody responses exists. Our study aimed to analyze the role of antibody response on prognosis and determine factors influencing the IgG antibodies’ seroconversion. 1111 patients with mild to moderate COVID-19 symptoms admitted to Leishenshan Hospital in Wuhan were retrospectively analyzed. A serologic SARS-CoV-2 IgM/IgG antibody test was performed on all the patients 21 days after the onset of symptoms. Patient clinical characteristics were compared. In the study, 42 patients progressed to critical illness, with 6 mortalities reported while 1069 patients reported mild to moderate disease. Advanced age (P=0.028), gasping (P<0.001), dyspnea (P=0.024) and IgG negativity (P=0.006) were associated with progression to critical illness. The mortality rate in critically ill patients with IgG antibody was 6.45% (95%CI 1.12%-22.84%) and 36.36% (95%CI 12.36%-68.38%) in patients with no IgG antibody (P=0.003). Symptomatic patients were more likely to develop IgG antibody responses than asymptomatic patients. Using univariable analysis, fever (P<0.001), gasping (P=0.048), cancer (P<0.001), cephalosporin (P=0.015) and chloroquine/hydroxychloroquine (P=0.021) were associated with IgG response. In the multivariable analysis, fever, cancer, cephalosporins and chloroquine/hydroxychloroquine correlated independently with IgG response. We determined that the absence of SARS-CoV-2 antibody IgG in the convalescent stage had a specific predictive role in critical illness progression. Importantly, risk factors affecting seropositivity were identified, and the effect of antimalarial drugs on antibody response was determined.